Comparison between the multiple‐set plus 2 weeks of tri‐set and traditional multiple‐set method on strength and body composition in trained women: a pilot study. (12th September 2014) - Garcia, Paula; Nascimento, Dahan da C.; Tibana, Ramires A.; Barboza, Maria M.; Willardson, Jeffrey M.; Prestes, Jonato
Summary: The manipulation of resistance training (RT) variables affects the neuromuscular adaptations and may also alter body composition. Another important factor to be considered is the presence of high, moderate and low responding subjects to training. The purpose of this study was to compare the effects of multiple‐set (MS) and tri‐set (TS) RT approaches on muscle strength and body composition following a 12 week programme in trained women (> 1 year of RT experience). A secondary objective was to assess variations in individual responsiveness to the RT by the identification of high (strength gains were > 20%), moderate (10 and 19%) and low responding (< 10%) subjects. Eleven healthy experientially resistance trained women were randomly divided into two groups: MS ( n  = 6; age 27·17 ± 8·23 years; body mass 57·97 ± 2·48 kg) and TS ( n  = 5; age 23·20 ± 2·28 years; body mass 61·74 ± 6·95 kg). High responders were found in the training groups (MS n  = 4 and TS n  = 1), moderate (MS n  = 1 and TS n  = 3) and low responders (MS n  = 1 and TS n  = 1). The MS group displayed an increase in squat 1RM ( P <0·01), stiff leg deadlift 1RM ( P <0·002) and squat repetitions maximum at 50% of 1RM ( P <0·04). The TS method significantly increased all strength variables ( P <0·05), with no differences between methods ( P >0·05). Differences were evident between subjects classified as high, medium and low responding in the stiff leg deadlift 1RM ( P  = 0·007). Both RT protocols increased strength, with no effect on body composition. The variability in individual responsiveness emphasizes the importance of individualized RT prescription for strength practitioners.